The need for a systemic approach to confront the crisis of antivenom availability and accessibility in Sub-Saharan Africa - Gutiérrez, José María (2019)
Resumen de trabajo presentado en XV CONGRESS OF THE BRAZILIAN SOCIETY OF TOXINOLOGY